Exploring the characteristics of kombucha tea fermented with soursop (Annona muricata), Noni (Morinda citrifolia) and pineapple (Ananas comosus) - Azizan Muhammad Adib; Qadir Rahman; Zakaria Mizatul Athila; Mohsin Aliah Zannierah; Meor Hussin Anis Shobirin (BIO Web of Conferences)
The current study aims to determine the physico-chemical and sensory properties of kombucha tea fermented with soursop (Annona muricata), noni (Morinda citrifolia), and pineapple (Ananas comosus) juices. The infused kombucha drink was prepared by adding 30% selected fruit juices in kombucha tea. It was fermented using SCOBY (symbiotic culture of bacteria and yeast) for 14 days at room temperature. The results revealed that the infusion of soursop, noni, and pineapple in kombucha tea contributed to increased pH value, Brix value, and higher percentage of yield biomass. Regarding color, the L, a, and b values of infused kombucha drinks were significantly different (p<0.05) from simple kombucha tea. There was also a significant difference (p<0.05) in proximate properties of infused and simple kombucha tea except for the crude protein content. The antioxidant analysis showed that addition fruit juices enhanced the antioxidant level of kombucha drinks. In case of sensory evaluation, it was observed that overall soursop and pineapple had higher overall acceptability followed by. The results of the current work indicate that the addition of selected fruit juices such as soursop, noni, and pineapple significantly improved the nutritional value and antioxidant attributes of kombucha tea and thus possess the opportunity to be marketed as a new tea with good flavor, taste and health prospects.